The Emotional Pathways Linking Mindfulness and Impulsive Buying Among Young Women Makeup Enthusiasts - Aulia, Sendi; Alamanda, Dini Turipanam; Anggadwita, Grisna; Kurniati, Dinar Mariam (Universitas Brawijaya, Indonesia, 2025)
In the digital era, the rise of social media marketing exposes young women to cosmetic advertisements, often triggering impulsive purchases. This study aims to explore the psychological and social factors influencing impulsive buying, focusing on how mindfulness affects beauty product purchases among young Indonesian women. Using a quantitative survey approach, data were collected from 321 Indonesian women aged 13–24 who use cosmetics. A non-probability sampling method was applied, and validity and reliability tests were conducted. Data analysis employed the Structural Equation Modelling (SEM) approach using IBM AMOS 26.0. Findings indicate that mindfulness does not directly influence impulsive buying but operates through fear of negative evaluation (FNE) and emotional intelligence (EI) as mediators. Mindfulness reduces impulsive purchases by lowering FNE, while EI has a significant negative effect on impulsive buying. This study underscores the importance of ethical marketing in the cosmetics industry, advocating for consumer education to curb impulsive spending and foster brand loyalty. Additionally, it highlights the need for emotional intelligence training to help young consumers make informed decisions. By revealing the indirect role of mindfulness through FNE and EI, this study contributes novel insights to the literature on adolescent women’s consumer behavior in Indonesia.